Assessment of Cancer Screening A Primer - Marcus, Pamela M. (Springer Nature, 2022)
Cancer screening is a prominent strategy in cancer control in the United States, yet the ability to correctly interpret cancer screening data eludes many researchers, clinicians, and policy makers. This open access primer rectifies that situation by teaching readers, in simple language and with straightforward examples, why and how the population-level cancer burden changes when screening is implemented, and how we assess whether that change is of benefit. This book provides an in-depth look at the many aspects of cancer screening and its assessment, including screening phenomena, performance measures, population-level outcomes, research designs, and other important and timely topics. Concise, accessible, and focused, Assessment of Cancer Screening: A Primer is best suited to those with education or experience in clinical research or public health in the United States - no previous knowledge of cancer screening assessment is necessary. This is the first text dedicated to cancer screening theory and methodology to be published in 20 years.